ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN PENGUNGKAPAN SOSIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Setiawati, Loh Wenny (Jurnal Akuntansi, 2018)
Economic growth that affects the welfare of the people can be pursued by investing. Investors will be interested to invest when the value of the company is high. Corporate value is an important concept for investors, because it is an indicator for the market to assess the company as a whole.  This study aims to examine the effect of profitability, firm size, leverage, and social disclosure of corporate value. This research uses purposive sampling method in conducting sample selection. The statistical method used to test the hypothesis is multiple linear regression analysis. This study uses 81 manufacturing industry companies listed on the Indonesia Stock Exchange in the period 2011-2015.  The results of this study indicate that profitability, firm size, leverage, and social disclosure affect the value of the company.